Detection of Melanocortin Receptor Type 4 (MC4R) Gene in Semen of Etawah Crossbreed and Senduro Goats - Belgania, Ristaqul Husna; Utomo, Budi; Mustofa, Imam; Kholifah, Yayuk; Amrullah, Muhammad Fajar (Universitas Airlangga, 2023)
Etawah crossbreed and Senduro goats as superior local goats and biological genetic resources that must be preserved in Indonesia. Melanocortin receptor type 4 (MC4R) is the primary gene that regulates food intake and energy balance which can be used as a candidate marker for livestock selection genes. This study aimed to analyze the comparison of cement quality and detect the profile of the MC4R gene in Etawah crossbreed and Senduro goat semen. The samples of this study were Etawah crossbreed and Senduro goat semen. Macroscopic examination of cement includes the evaluation of volume, consistency, odor, color, and pH. Microscopic examination of semen includes motility, abnormalities, and spermatozoa concentration. Examination of motility was performed in the condition of fresh semen, after the addition of diluents, and post-thawing of frozen straw. The polymerase chain reaction (PCR) method was performed to amplify specific fragments of the MC4R gene. There was a decrease in spermatozoa motility before freezing and post-thawing frozen semen compared to fresh semen. The quality of frozen straw post-thawing Etawah crossbreed and Senduro goat was still worth using for artificial insemination and in vitro embryo production. The MC4R gene can be detected in liquid and frozen semen from Etawah crossbreed and Senduro goats using a PCR test in the form of a single band along 642 bp.